2014
DOI: 10.1007/s00441-013-1781-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combinations of BMP-2 with FGF-2 and/or VEGF on HUVECs angiogenesis in vitro and CAM angiogenesis in vivo

Abstract: Angiogenesis, a complex biologic process, is regulated by a large number of angiogenic factors, including vascular endothelial growth factor (VEGF) and fibroblast growth factor-2 (FGF-2). Whether Bone morphogenetic proteins-2 (BMP-2), the osteoinductive factor, could significantly reinforce the effect of VEGF and FGF-2 on angiogenesis has not been studied in detail. To study the positive effects of multiple growth factors on angiogenesis, HUVECs were treated with BMP-2, VEGF, or FGF-2 singly and in binary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 33 publications
2
46
1
Order By: Relevance
“…BMP2, 4, 6 and 7 have been reported to increase VEGF levels, to enhance capillary tube formation, to promote the proliferation and migration of ECs during the activation phase of angiogenesis, and to regulate the physiology of mural cells during the maturation phase [141,142]. In contrast, antiangiogenic responses have also been reported in other studies, again depending on the BMP dose and cellular context [143,144].…”
Section: Endoglin Expression Modifies Angiogenesis and Vascular Remodmentioning
confidence: 47%
“…BMP2, 4, 6 and 7 have been reported to increase VEGF levels, to enhance capillary tube formation, to promote the proliferation and migration of ECs during the activation phase of angiogenesis, and to regulate the physiology of mural cells during the maturation phase [141,142]. In contrast, antiangiogenic responses have also been reported in other studies, again depending on the BMP dose and cellular context [143,144].…”
Section: Endoglin Expression Modifies Angiogenesis and Vascular Remodmentioning
confidence: 47%
“…Therefore, in the present study, both BMP-2 and VEGF were applied to the bone defect. One previous study found that BMP-2 could amplify the angiogenic activity of VEGF [20]. However, there is an ideal and specific ratio of BMP-2:VEGF for new bone formation [21].…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2 has previously been shown to promote angiogenesis ex vivo in mouse bones explants. [ 53 ] Moreover, in vitro BMP-2 directly activated ECs and promoted migration in transwell and scratch migration assays [ 54 ] as well as the formation of microvascular structures on matrigel. [ 55,56 ] However, in our hydrogels the stimulation with BMP-2 or FGF-2 is not suffi cient to support the formation of vascular structures by HUVECs in monocultures ( Figure S1a, Supporting Information; data not shown for BMP-2).…”
Section: D Cocultures Can Be Directed Toward Osteogenically Differenmentioning
confidence: 99%